The Implementation of Local Culture on the Development of Reception Orale Teaching Materials through YouTube Media - Nurilam Harianja; Hesti Fibriasari; T. Ratna Soraya (Britain International for Academic Research (BIAR) Publisher, 2020)
The development of receptional orale teaching materials based on local culture through YouTube aims to help learners understand French language with the situation of local culture. The development of teaching materials using YouTube which is implemented in learning is very important to improve listening skills by French language learners. Besides this local culture-based video uploaded on YouTube will be very useful for French tourists visiting Indonesia, especially Medan. Therefore this video will present the real situation in Medan, for example, when making a reservation through the application for transportation or for others. The research method uses Research and Development that will be implemented in the French Language Education Study Program by developing teaching materials based on local culture to improve listening skills by Unimed French language students.